2022
DOI: 10.1021/acs.biochem.2c00460
|View full text |Cite
|
Sign up to set email alerts
|

Negative Cooperativity in the Mechanism of Prenylated-Flavin-Dependent Ferulic Acid Decarboxylase: A Proposal for a “Two-Stroke” Decarboxylation Cycle

Abstract: Ferulic acid decarboxylase (FDC) catalyzes the reversible carboxylation of various substituted phenylacrylic acids to produce the correspondingly substituted styrenes and CO2. FDC is a member of the UbiD family of enzymes that use prenylated-FMN (prFMN) to catalyze decarboxylation reactions on aromatic rings and C–C double bonds. Although a growing number of prFMN-dependent enzymes have been identified, the mechanism of the reaction remains poorly understood. Here, we present a detailed pre-steady-state kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recent studies on UbiD-like enzymes have suggested the importance of domain motions in catalysis. For example, stopped-flow spectroscopy indicates that the dimeric UbiD-like enzyme FDC exhibits negative cooperativity between the two subunits arising from a conformational change that facilitates inter-conversion between the “fast, tight” and the “slow, loose” active sites ( 46 ). Studies on vanillic acid decarboxylase suggest that “open” and “closed” conformers of the enzyme have different affinities for reaction intermediates that may be important for catalysis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on UbiD-like enzymes have suggested the importance of domain motions in catalysis. For example, stopped-flow spectroscopy indicates that the dimeric UbiD-like enzyme FDC exhibits negative cooperativity between the two subunits arising from a conformational change that facilitates inter-conversion between the “fast, tight” and the “slow, loose” active sites ( 46 ). Studies on vanillic acid decarboxylase suggest that “open” and “closed” conformers of the enzyme have different affinities for reaction intermediates that may be important for catalysis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The UbiD pfam of putative prFMN-dependent (de)­carboxylases now contains over 35 000 sequences, pointing to the widespread occurrence of this class of enzymes in microbes. There has been a significant expansion of our knowledge surrounding the mechanisms, structures, and substrate range ,,, of these enzymes since the first prFMN-dependent enzyme, FDC, was described in 2015 . However, the biosynthesis of the prFMN cofactor has received much less attention.…”
Section: Discussionmentioning
confidence: 99%